PEMBERDAYAAN USAHA KECIL KOPRA DI DESA SAPA KECAMATAN TENGA KABUPATEN MINAHASA SELATAN - RANTUNG, VINCENT; OGOTAN, MARTHA; TAMPI, GUSTAAF BUDI (Sam Ratulangi University, 2018)
Micro Enterprises Based on Law Number 20 of 2008 concerning MSMEs (Small and Micro MediumEnterprises) are productive businesses owned by individuals and / or individual business entities that meet thecriteria of Micro Enterprises as stipulated in this Law. But there are problems of Kopra Small Business in SapaKecamata Tengah Village, South Minahasa Regency, which are unstable prices, declining prices, no capitalassistance and copra processing facilities from the local government and decreased production due to coprafarmers who are reluctant to produce copra because copra prices have not in accordance with the cost of living.To measure the success of copra research empowerment using the concept according to Edi Suharto, namely:Possibility, Strengthening, Protection, Improvement, and Maintenance. This study uses a qualitative method. Theinformants in this study were seven people. Data collection techniques used were interviews, observation anddocumentation. the results of research obtained in the copra business empowerment in the village of Sapa aredone individually and on a household scale. Empowerment of the copra business in Sapa Village has receivedless attention from the government that there is no capital assistance and tools to support copra work directlyfrom the government. It is not yet apparent that the village government's efforts to voice the aspirations of coprafarmers and entrepreneurs. The hope of the researchers is that the Sapa Village government to innovate propeoplepolicies and programs such as being actively involved in copra business empowerment in Sapa Village sothat copra can be developed into food, cosmetics and ingredients and oils such as Virgin coconut oil. the Sapavillage government must dare to convey the aspirations of the copra farmer groups to the district level and theremust be concrete actions from the government to provide capital and empowerment of copra into other derivativeproducts. The need for economic institutions, such as village savings and loan cooperatives and theimplementation of BUMDES must touch on every farmer group and copra businessman in Sapa Village.Keywords: Empowerment, of Society, Small Businesses.